Zitate der >Aeneis< in den Briefen des Hieronymus Eine digitale Intertextualitätsanalyse zur Untersuchung kultureller Transformationsprozesse - Revellio, Marie (Philologus. Supplemente / Philologus. Supplementary Volumes, 2022)
In his letters, the church scholar Jerome describes a deep inner rift between Virgil and the gospels, between Cicero and the apostles. This volume traces late ancient processes of cultural hybridization using methods from digital quote analysis. By looking at quotes from the Aeneid, it examines the narrative strategies employed by Jerome to process the tension-filled relationship between classical antiquity and Christianity.